Efektivitas Penyaluran Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Desa Tabing Kecamatan Koto Kampar Hulu Kabupaten Kampar - Nur Ainaini; Ratna Dewi (Al-Manar Journal of Economic and Social Studies, 2025)
The development of the Community-Based Drinking Water and Sanitation Program (PAMSIMAS) has improved the welfare of the community, particularly in the health sector. Although this program has made the community happy by providing easy access to clean water at home, research has identified distribution issues in Desa Tabing, such as pipe damage, irregular water distribution, and differences in water pressure due to the elevation of the houses. The aim of this study is to assess the effectiveness of water distribution in PAMSIMAS in Desa Tabing, Koto Kampar Hulu Subdistrict, Kampar Regency, and the factors influencing it. This study uses Gibson's theory to measure effectiveness, including productivity, efficiency, satisfaction, excellence, and development. The research employs a qualitative descriptive method. Data was collected through observation, interviews, and documentation. Informants in this study were selected using purposive sampling, and data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results of the study show that the effectiveness of the Community-Based Drinking Water and Sanitation Program (PAMSIMAS) in Desa Tabing, Koto Kampar Hulu Subdistrict, Kampar Regency, has been implemented well, although it has not yet fully achieved 100% of its targets. Several factors that influence this effectiveness include community awareness and geographical differences.